Current Situation and Management of Pleural Effusion in PHI Clinical Hospital Tetovo - Ruzhdi Rexhepi; Selma Arifi; Merita Rexhepi; Dejan Dokic; Tatjana Ruskovska (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Pleural effusion is a disturbance in the balance between fluid production and elimination in the pleural space, resulting in abnormal fluid accumulation. It can result from various medical conditions related to the lungs and pleura or systemic diseases. Identifying the etiology of pleural effusion is essential for effective treatment. According to Light's criteria, pleural effusions are transudative and exudative.